Factors Related to Community Waste Management in Kota Baru Sub District Jambi City in 2022 - Willia Novita Eka Rini; Fajrina Hidayati; Marta Butar Butar; Oka Lesmana; Diani Lahanavia Rahayu (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Waste that is not managed properly can cause environmental pollution and health problems. This study is to find out what factors are related to waste management in the community to reduce the amount of waste generation in Kota Baru SubDistrict, Jambi City. This study used an analytical survey method with a cross-sectional. The population in this study was 80,062 families with a sample of 106 respondents with a sampling technique using stratified random sampling. The independent variables in this study were knowledge, attitudes, subjective norms and control over behavior, while the dependent variable was waste management. The measuring tools used are observation sheets and questionnaires. Data analysis was carried out univariate and bivariate (using chi-square = 0.05).  The results showed that there was no relationship between attitudes (p value = 0.132), subjective norms (p value= 0.138) with waste management and there is a relationship between behavioral control (p value = 0.00), knowledge (p value = 0.00) with waste management. From the results of this study, knowledge and control of behavior greatly affect waste management. It is suggested to increase public knowledge by providing information in the form of posters and so on as well as increasing waste management facilities.